Smad7 Antisense Oligonucleotide in Crohn's Disease: A Re-Evaluation and Explanation for the Discordant Results of Clinical Trials - Giovanni Monteleone; Carmine Stolfi (MDPI AG, 2022)
In Crohn's disease (CD) and ulcerative colitis (UC), the major inflammatory bowel diseases (IBD) in human beings, the tissue-damaging inflammatory response is characterized by elevated levels of Suppressor of Mothers Against Decapentaplegic (Smad)7, an inhibitor of the immunosuppressive cytokine Transforming Growth Factor (TGF)-β1. Consistently, preclinical work in mouse models of IBD-like colitis showed that the knockdown of Smad7 with an antisense oligonucleotide (AS) attenuated the mucosal inflammation, thus paving the way for the development of an AS-containing pharmaceutical compound, named mongersen, for clinical use. The initial phase 1 and phase 2 studies showed that oral administration of mongersen was safe and effective in inducing clinical remission in active CD patients. However, subsequently, a large multicentered, randomized, double-blind, placebo-controlled, phase 3 trial was prematurely discontinued because of an interim analysis showing no effect of mongersen on the activity of CD. In this study we will discuss recent data showing that the majority of the batches of mongersen used in the phase 3 study were chemically different from those used in the previous clinical trials, with some of them being unable to knockdown Smad7 in cultured cells. The accumulating evidence highlights the need to maintain consistent manufacturing requirements for clinical AS, as well as the potential benefits of in vitro bioassays as a part of quality control. New clinical trials evaluating mongersen's impact on IBD using chemically homogenous batches will be needed to ascertain the therapeutic efficacy of such a drug.